Analisis Yuridis Peraturan Menteri Agama Nomor 20 Tahun 2019 Terhadap Praktik Itsbat Nikah Di Bawah Umur: Studi Kasus Di Kantor Urusan Agama Kecamatan Bulango Ulu Kabupaten Bone Bolango, Provinsi Gorontalo - Suharyono Paputungan; Nurmin K. Martam; Robby Waluyo Amu; Yayan Hanapi; Ibrahim Ahmad (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
The urgency of marriage as an effort to elevate human dignity and sustain life and progeny is regulated in Law Number 16 of 2019, which amends Law Number 1 of 1974 concerning Marriage. The state requires marriage registration to guarantee the validity and legal protection of the rights of married couples and their children. One important provision in this regulation is the determination of the minimum age for marriage, which is 19 years for both men and women. However, in practice, underage marriages, including unregistered marriages, still occur. This study uses a normative-empirical research method, combining written legal analysis with field data to examine the application of laws and regulations in community practice. The results show that underage marriages can be legalized by the Religious Court based on Minister of Religious Affairs Regulation Number 20 of 2019. This regulation provides legal certainty and protection of children's rights, but has also raised controversy regarding the potential legalization of early marriage. This regulation has had a significant impact on the practice of itsbat nikah anak kecil, especially at the Bulango Ulu Religious Affairs Office (KUA), by reducing unregistered marriages. However, challenges in verifying evidence, socio-cultural pressures, and the normalization of early marriage remain major obstacles that must be overcome through education and cross-sector collaboration.